Liu Kang Essays on Art and Culture - Liu, Kang (National Gallery Singapore, 2011)
Liu Kang: Essays on Art and Culture is a testament to the inexorable passion of an artist who knew no boundaries. This collection of essays, which Liu Kang wrote over 44 years, offers an insight into the artist's myriad interests as well as his contributions as a first generation Nanyang artist and art educator. Translated into English for this volume, Liu Kang's essays are accompanied by commentaries and photographs of the artist-author and his subjects.